1981
DOI: 10.1177/002221948101400615
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of Learning Disabled Students in the Mainstream Environment

Abstract: The sociometric status of primary and upper elementary students was investigated. The locale was a suburban area where those children classified as learning disabled were mainstreamed in two elementary schools. There were 362 children participating in the study, 8% of whom were learning disabled. The data do not support the findings of previous studies on the sociometric status of handicapped children in the regular classroom; i.e., learning disabled children would rate significantly lower in terms of populari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
1
2

Year Published

1983
1983
2004
2004

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 12 publications
0
9
1
2
Order By: Relevance
“…However, two recent studies, one utilizing a nomination technique and one utilizing a rating scale, revealed no significant differences in the social status of LD children and their regular class peers (Prillaman, 1981;Sainato, Zigmond, & Strain, 1983). These results challenge previous conclusions regarding the social acceptance of LD children and emphasize the need for further research.…”
Section: Sociometric Assessmentcontrasting
confidence: 59%
See 1 more Smart Citation
“…However, two recent studies, one utilizing a nomination technique and one utilizing a rating scale, revealed no significant differences in the social status of LD children and their regular class peers (Prillaman, 1981;Sainato, Zigmond, & Strain, 1983). These results challenge previous conclusions regarding the social acceptance of LD children and emphasize the need for further research.…”
Section: Sociometric Assessmentcontrasting
confidence: 59%
“…Many of the problems that occur with regular class placements have been related to social competence issues and to our lack of knowledge about ways to enhance social competence (Asher & Taylor, 1981 1974;Sheare, 1974), emotionally disturbed (Co wen et al, 1973;Weintraub, Prinz, & Neale, 1978), and physically handicapped (Elser, 1959;Force, 1956). Investigations have also been extended to include learning disabled children (Bryan, 1974;Bruininks, 1978a;Prillaman, 1981;Sheare, 1978;Siperstein, Bopp, & Bak, 1978). However, these latter studies have been concerned with describing the social status of learning disabled students who receive either resource room services, tutorial services, or some other type of part-time supportive services.…”
mentioning
confidence: 99%
“…Numerous studies have reported peer difficulties for students with LD (see Pearl et al, 1986, andWiener, 1987, for reviews), including lower peer acceptance than other students (e.g., Bursuck, 1989;Gresham & Reschly, 1986;La Greca & Stone, 1990). A few exceptions exist, particularly when achievement is controlled (e.g., Bursuck, 1983;Prilliman, 1981;Vaughn, Haager, Hogan, & Kouzekanani, 1992;Vaughn, Mcintosh, Schumm, Haager, & Callwood, 1993). This study sought to extend and clarify previous findings related to peer acceptance of students with LD.…”
Section: Peer Acceptancementioning
confidence: 99%
“…In fact, these studies have shown that some members of LD samples perform as well as (e.g., , and are as well liked as (e.g., Perlmutter et al, 1983;Prillaman, 1981), their nonhandicapped peers. Consequently, not all members of the LD population need training in social skills.…”
Section: The Content Of Social Skills Interventions For Ld Individualsmentioning
confidence: 99%